Readability Assessment of English Junior High School Textbooks by Implementing Cloze Procedure - Rita Karmila Sari (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
Textbooks that are too difficult to read will decrease students’ motivation in learning, while textbooks that are too easy to read will make students less interested in reading them. Therefore, the readability analysis needs to be done so that the textbooks used as learning media are suitable for the students who become the target readers of the books. This study analyzes the texts in Junior High School English textbooks entitled “English in Focus” grades VII, VIII, and IX published by the Center of Book Archieve of the Department of National Education by using cloze procedure. The tests were carried out in SMPN 1 Gunungputri and SMP Sejahtera 2 Cileungsi, involving students in grades VII, VIII, and IX. The texts tested were adapted to their grade levels. The tests were made in the form of 100 words which were then omitted at every 5th word. The readability results of “English in Focus” textbook are that not all texts in the book are suitable for students who use it. If the books are considered as suitable teaching material, these books need some changes because there are 6 texts from the total of 24 texts that are considered too difficult for students.Keywords: textbook assessment, readability, cloze procedure